Holistic Pedagogy The Self and Quality Willed Learning - Ricci, Carlo; Pritscher, Conrad P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book illuminates what must always be at the heart of powerful schooling and authentic learning. Its focus is on free learning, with an emphasis on early East Asian thought as a vehicle through which learning may emerge. The volume describes learning as helping the learner become more conscious, more aware. As such the authors explain how quality learning encompasses all learning that is chosen by the learner. It is non-judgmental and their idea is that if learning is done by choice then direct harm will be mitigated because quality, willed learning is not just about the individual, but includes others $1 (Bit is community focused as well as self-determined. In the first part of the volume the authors look specifically at how quality willed learning can inform the state and how it can protect the rights of children. The second part looks at what quality willed learning can mean to leaders. In the last part the authors look at what it can mean for teachers and finally what it can mean for the learners themselves.s
Chapter 1. Getting It - Evaluating Teachers and Learning -- Chapter 2. Another Major Problem. - Theories Are Not Physical -- Aspects of Science -- Chapter 3. The Process of Coming to Know. - What Is Evident About Evidence? Chapter 4. Structuring Learning -- Ordering -- The Study of Genes and Learning -- School Malpractice -- Chapter 5. Quality Learning and Productive Perplexity -- Between Specialization and Generalization -- Noticing Problems -- Gene Study and Schooling -- Resiliency -- The Power of Self-determined Neuroplasticity -- Chapter 6. Throwing Tea in Schooling$1 (Bs Harbor -- The Content of Processing and the Processing of Content -- Chapter 7. Instructions for Instructing -- A Kind of Schooling: A Kind School -- Alexander Inglis as a Continual Problem -- Chapter 8. Quality Teaching and Uncommon Ways -- Measuring the Process of Measuring -- Quality Teaching and Effective Teaching -- Quality Learning and Abstractions -- Chapter 9. (3z(BIt(3y (BIs Difficult To Say -- Words and Quality Learning -- Explaining Quality Learning -- The Teacher: Not the Subject -- Quality Willed Learning and Present Experience.s
Keywords: Education; Teaching; Education; Learning & Instruction; Teaching and Teacher Education; Electronic books